2017
DOI: 10.1038/lsa.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal display and organic light-emitting diode display: present status and future perspectives

Abstract: Recently, ‘Liquid crystal display (LCD) vs. organic light-emitting diode (OLED) display: who wins?’ has become a topic of heated debate. In this review, we perform a systematic and comparative study of these two flat panel display technologies. First, we review recent advances in LCDs and OLEDs, including material development, device configuration and system integration. Next we analyze and compare their performances by six key display metrics: response time, contrast ratio, color gamut, lifetime, power effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
427
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 781 publications
(472 citation statements)
references
References 171 publications
0
427
0
4
Order By: Relevance
“…TL in this case arises by decay of excited states in the form of fluorescence (FL) or phosphorescence (PH). A significant feature of this phenomenon is that it can readily provide insights into reactivities of radical ions, that play an important role not only in TL but also in photoredox reactions and organic electronic devices …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TL in this case arises by decay of excited states in the form of fluorescence (FL) or phosphorescence (PH). A significant feature of this phenomenon is that it can readily provide insights into reactivities of radical ions, that play an important role not only in TL but also in photoredox reactions and organic electronic devices …”
Section: Methodsmentioning
confidence: 99%
“…A significant feature of this phenomenon is that it can readily provide insights into reactivities of radical ions, [3,4] that play an important role not only in TL but also in photoredox reactions [5,6] and organic electronic devices. [7][8][9] Previously, we reported that γ- [10,11] or X-ray [12] irradiation of methylcyclohexane (MCH) matrices (77 K) containing 2-aryl-1methylene-2-phenylcyclopropanes 1 (Scheme 1) followed by annealing leads to TL at around 130 K. For example, the 2,2diphenyl derivative 1 a displays vivid green TL. Emission in this case was assigned to triplet-triplet fluorescence (TÀ T FL) arising from the excited triplet state of the ring opened trimethylenemethane (TMM) biradical 3 2 a ** *.…”
Section: Rates Of Ring Opening Of Radical Cation Intermediates Governmentioning
confidence: 99%
“…To achieve HDR and good sunlight readability, high contrast ratio (CR>10 5 :1), high peak luminance (at least 1000 cd/m 2 ) and excellent dark state (0.01 cd/m 2 ) of the display system are required. However, both of the two leading display technologies, liquid crystal display (LCD) and organic light-emitting diode (OLED) need substantial improvements to fulfill these requirements [3]. First of all, OLED is relatively easy to display true black state, but to achieve a luminance >1000 cd/m 2 requires a relatively high current, which would compromise the lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…LCD and OLED are the 2 main competing technologies with their own merits in flat panel display. Liquid crystal displays (LCDs) are widely used in applications from small‐sized cell phones, medium‐sized computer monitors, to large‐sized televisions.…”
Section: Introductionmentioning
confidence: 99%